Razvoj fizične geografije na ljubljanski univerzi - Lovrenčak, Franc (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
The paper is an attempt to present the development of physical geography at the Department of Geography at the Ljubljanaćs Faculty of Arts. The last two decades, from 1989 to 2009, are discussed, trying to include all its branches,forming the Chair of physical geography during this period. The presentation of physical geographers, who worked as researchers and teachers in particular branches of physical geography, should demonstrate the way and degree of studying physical-geographical characteristics of, mainly, Slovenian landscapes.
Keywords: fizična geografija; physical geography; Slovenia; Slovenija; teorija; theory; visokošolski študij